Sejarah Pemikiran Psikologi Islam Zakiah Daradjat - Nunzairina Nunzairina (UIN Sumatera Utara Medan, 2018)
Speaking of Islamic Psychology in Indonesia, it can not be separated from Zakiah Daradjat's contribution. He is an early figure who brought and developed Islamic Psychology in Indonesia. In addition to being an outstanding lecturer at several universities, his contribution is also reflected through his works. Scientists from Bukittinggi argue that Islamic psychology is closely related to Islamic education and mental health. and piety. Based on the uniqueness, this research will discuss related biography Zakiah Daradjat and his thinking about Islamic psychology. This study uses historical research methods with heuristic stages, verification, interpretation, and historiography. The results of this study is Zakiah Daradjat who was born on 6 November 1926 is the first Muslim psychologist in Indonesia who contribute greatly in the world of psychology and Islamic education. His contribution can be seen from his efforts and his work in these two fields. he argues that Islamic education has a close relationship with religious psiology and mental health. Bad phenomena that occur in the world of education today, will be overcome by using religious psychology as an approach in Islamic education. Thus, students will create mental health based on religion.Keywords: Thought, Zakiah Daradjat, Islamic Psychology.